Front Cover: Phosphinine Selenide: Noncovalent Interactions with Organoiodines and Elemental Iodine, and Reactivity towards Potassium Cyanide (ChemPlusChem 4/2023). Issue 4 (9th March 2023) - Lin, Jinxiong; Coles, Nathan T.; Weber, Manuela; Müller, Christian
Abstract : The front cover picture illustrates that the title compound serves as a multifunctional molecule. It can form non‐bonding interactions, such as π‐π stacking, hydrogen bonding, F‐F‐ and Se‐I contacts with several substrates and acts as an efficient selenium transfer reagent. More information can be found in the Research Article by Christian Müller and co‐workers .